2020
DOI: 10.30795/jfootankle.2020.v14.1185
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of early complications in the posterolateral approach to posterior malleolus fractures

Abstract: Introduction: To ascertain the incidence of early complications in the posterolateral approach to open reduction and internal fixation of posterior malleolar fractures and identify possible risk factors related to occurrence of these complications. Methods: Retrospective study carried out in three tertiary hospitals. Patients who underwent open reduction and internal fixation of posterior malleolus fractures via the posterolateral route were divided into two groups: with versus without delayed postoperative he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…A recent study by Tavares et al also explored wound complications among posterior malleolus fractures surgically treated in the posterolateral approach through a single window. 7 Their wound complication rate of 44.2% is higher than our findings and that of Little et al 7,16 In surgically treated geriatric ankle fractures, Aigner et al 1 had wound complications in just 9.7% of cases, making our 12.0% finding relatively high despite being younger with an average age of 49.3 years.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…A recent study by Tavares et al also explored wound complications among posterior malleolus fractures surgically treated in the posterolateral approach through a single window. 7 Their wound complication rate of 44.2% is higher than our findings and that of Little et al 7,16 In surgically treated geriatric ankle fractures, Aigner et al 1 had wound complications in just 9.7% of cases, making our 12.0% finding relatively high despite being younger with an average age of 49.3 years.…”
Section: Discussioncontrasting
confidence: 50%
“…Still, the high rate found by Tavares implies that the single-window approach is also susceptible to similar issues. 7…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of ankle fractures involving the PM has undergone considerable changes over the past decade [4][5][6][7][8][9][10][11][12][13]. The aim of our study was to identify risk factors for complications following surgical treatment in a sizeable number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Pinho-Tavares et al [ 13 ] reported 44% (19/43) delayed wound healing with the posterolateral approach and referred to a considerable learning curve. Mertens et al [ 12 ] saw a hallux flexion deficit in 30% and sural nerve lesions in even 38% of 50 patients treated via a posterolateral approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation